Analisis Pengaruh Stock Split terhadap Harga Saham dan Volume Perdagangan Saham pada Perusahaan Go Public di BEI Periode 2018-2021 - Axelino, Tristan; Adam, Mohamad; Andriana, Isni (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to determine the effect of stock splits on stock prices and stock trading volume in companies listed on the Indonesia Stock Exchange. The technique in this study uses samples from purposive sampling by differentiating companies taking actions from stock splits during the 2018-2021 period. The population in this study are companies that carry out stock split actions that are listed on the Indonesia Stock Exchange (IDX), totaling 34 companies. The period in this study was 7 days before and 7 days after the stock split. Data analysis used the normality test using One-sample Kolmogorov Smirnov to test whether the data was normally distributed or not. Data that is normally distributed uses the Paired Sample T-test and data that is not normally distributed uses the Wilcoxon Signed Ranked Test. The results of this study indicate that there is no difference in stock prices after the stock split and there is a difference in the volume of stock trading after the stock split. Keywords: Stock Split, Stock Price, Trading Volume